1970
DOI: 10.1254/jjp.20.517
|View full text |Cite
|
Sign up to set email alerts
|

Response to Sympathetic Nerve Stimulation and Noradrenaline in Atria Treated With Reserpine and in Atria From Rabbits Pretreated With Reserpine

Abstract: It is widely known that cardiac noradrenaline is markedly depleted by pretreat ment of animals with reserpine (1) but only slightly reduced by treatment of the isolated heart with reserpine (2, 3). Pretreatment of animals with reserpine depresses the reten tion of exogenous noradrenaline in the heart (4) by reducing the uptake of the amine by storage granules (5) and by increasing the destruction of the amine by monoamine oxidase in sympathetic nerve terminals (6). Reserpine when applied in vitro significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1972
1972
2003
2003

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…It is generally accepted that the intragranular pool is a functional or available NA storage site that is more readily released by nerve impulses 17,18 . Those conclusions are supported by observations in isolated atria from reserpine‐treated guinea‐pigs, rabbits and cats that show that refilling of the NA stores restores responses of the atrial pacemaker to tyramine, but not to sympathetic nerve stimulation 19,21 . In contrast with those reports, we found that not only tyramine‐induced, but also nerve stimulation‐induced adrenergic responses were consistently restored after replenishment of NA, as demonstrated previously in the guinea‐pig vas deferens 22 and cat nictitating membrane 23 .…”
Section: Discussionmentioning
confidence: 87%
“…It is generally accepted that the intragranular pool is a functional or available NA storage site that is more readily released by nerve impulses 17,18 . Those conclusions are supported by observations in isolated atria from reserpine‐treated guinea‐pigs, rabbits and cats that show that refilling of the NA stores restores responses of the atrial pacemaker to tyramine, but not to sympathetic nerve stimulation 19,21 . In contrast with those reports, we found that not only tyramine‐induced, but also nerve stimulation‐induced adrenergic responses were consistently restored after replenishment of NA, as demonstrated previously in the guinea‐pig vas deferens 22 and cat nictitating membrane 23 .…”
Section: Discussionmentioning
confidence: 87%
“…Inhibition of monoamine oxidase does not affect the failure of noradrenaline to restore responses in rabbit atria (TODA et al, 1970).…”
Section: Recovery Of Adrenergic Function After Reserpinementioning
confidence: 86%